2022
DOI: 10.3171/2022.1.spine211418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local intraoperative epidural use of triamcinolone acetonide–soaked Gelfoam on postoperative outcomes in patients undergoing posterolateral lumbar spinal fusion surgery: a randomized, placebo-controlled, double-blind trial

Abstract: OBJECTIVE Prior evidence has supported the use of local intraoperative epidural steroids in lumbar discectomy for improvements in postoperative pain and outcomes. However, currently there is a paucity of data regarding the efficacy of local epidural steroids in spinal fusion procedures. The present investigation aimed to evaluate the impact of local epidural administration of triamcinolone acetonide–soaked Gelfoam on postoperative pain and patient-reported outcomes in patients undergoing instrumented posterola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…[1] In the Tavanaei et al series, in which they applied steroid-soaked Gelfoam on dura at the end of fusion surgery four (8.0%) patients in the treatment and two (4.0%) in the control groups, respectively, developed postoperative surgical site infections (i.e., although not statistically significant). [6] CONCLUSION e literature showed that ESI within 30 days to 6 months before spinal surgery increases the risk of both superficial and deep postoperative spinal infections. Further, this study indicated that the additional intraoperative administration of ESI increased the risk of both superficial (i.e., 4 of 23) and deep…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] In the Tavanaei et al series, in which they applied steroid-soaked Gelfoam on dura at the end of fusion surgery four (8.0%) patients in the treatment and two (4.0%) in the control groups, respectively, developed postoperative surgical site infections (i.e., although not statistically significant). [6] CONCLUSION e literature showed that ESI within 30 days to 6 months before spinal surgery increases the risk of both superficial and deep postoperative spinal infections. Further, this study indicated that the additional intraoperative administration of ESI increased the risk of both superficial (i.e., 4 of 23) and deep…”
Section: Discussionmentioning
confidence: 99%
“…series, in which they applied steroid-soaked Gelfoam on dura at the end of fusion surgery four (8.0%) patients in the treatment and two (4.0%) in the control groups, respectively, developed postoperative surgical site infections (i.e., although not statistically significant). [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies ultimately concluded that ESBs reduced pain scores, opioid consumption, and extended time to first analgesics. Conversely, Tavanaei et al reported that local intraoperative epidural use of triamcinolone acetonide-soaked Gelfoam did not provide any significant benefit in 100 patients undergoing posterolateral lumbar spinal fusion [ 48 ]. Furthermore, RCTs studies are needed which focus on novel techniques in order to implement a standardized universal protocol and mitigate the dependance on opioids.…”
Section: Regional Anesthesiamentioning
confidence: 99%